2021
DOI: 10.3390/ani12010070
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Olkuska Sheep Milk for the Production of Symbiotic Dairy Ice Cream

Abstract: The aim of this study was to determine the possibility of using Olkuska sheep milk for the production of ice cream with probiotics and prebiotics. The study examined the effect of the storage and type of bacteria used for the fermentation of ice cream mixes and partial replacement of inulin with apple fiber on the physicochemical properties, viability of probiotic cultures and organoleptic properties of sheep’s milk ice cream stored at −22 °C for 21 days. The addition of apple fiber reduced the pH value of ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…However, the differences could result from the fact that overrun values have a high dependence on the type of freezer used. Kowalczyk et al [ 37 ] also observed that the freezing process reduced the population of probiotic bacteria cells in sheep´s milk ice cream with inulin from 0.8, 1.0 and 1.1 log CFU/g in products with L. acidophilus LA-5, Lacticaseibacillus paracasei L-26, and Lacticaseibacillus casei 431, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the differences could result from the fact that overrun values have a high dependence on the type of freezer used. Kowalczyk et al [ 37 ] also observed that the freezing process reduced the population of probiotic bacteria cells in sheep´s milk ice cream with inulin from 0.8, 1.0 and 1.1 log CFU/g in products with L. acidophilus LA-5, Lacticaseibacillus paracasei L-26, and Lacticaseibacillus casei 431, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The production of ovine’s and caprine’s yoghurts and frozen yoghurts has also followed this trend. Several research works refer to the use of ewe’s [ 32 , 33 , 34 , 35 , 36 , 37 ] and goat’s [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] milks in the production of ice creams with functional properties. In addition, several authors reported the potential medicinal properties of small ruminant’s milks and dairy products [ 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five groups of inoculum were prepared according to the method of Mituniewicz-Małek et al [ 51 ] and Kowalczyk et al [ 52 ]. Previously revived monocultures of probiotic bacteria, in the amount of 10 mg L −1 ( w/w ), were activated at 40 °C until the pH was 4.60 ± 0.10.…”
Section: Methodsmentioning
confidence: 99%
“…moulded ice cream, conformability is directly related to the sensory effects and palatability of the ice cream product; therefore, in the production of ice cream, it is necessary to ensure that the product shape is maintained in the best condition to win over the consumer [27][28][29]. Figures 6-8 show the melting state of ice cream prepared with different CAS species.…”
Section: Ice Cream Conformabilitymentioning
confidence: 99%